The Analysts’ Forecast of IPO Firms During the Global Financial Crisis - Hsu, Chang-Yi; Yu, Jean; Wen, Shiow-Ying (International Journal of Economics and Financial Issues, 2013)
In this study, we examine the analysts’ behavior in the pre-crisis and post-crisis period for IPO firms in the U.S. from 2005 to 2011. By controlling variables size, the proxy of underpricing, the number of the IPO firms and whether the company is listed on NYSE or NASDAQ, we investigate the forecast error of analyst between pre-crisis and post-crisis period for 2008 global financial crisis. The result shows that analysts in our sample are optimistic, and they would become more optimistic after financial crisis. Conservative analysts would emphasize determinants of variables when valuing IPO firms to make their predictions before financial crisis but only consider the prior-year earnings change after financial crisis. Contrarily, analysts more optimistic notice whether the company is listed on NYSE or NASDAQ before crisis but also consider the factors of debt ratio, firm size and the market trends. Keywords: IPO; Analysts’ forecast; Financial crisis JEL Classifications: G01; G15; G30